2021
DOI: 10.21203/rs.3.rs-241147/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant Developmental Stage Drives the Differentiation in Ecological Role of Plant Bacterial and Fungal Microbiomes

Abstract: BackgroundPlants live with diverse microbial communities which profoundly affect multiple facets of host performance such as nutrition acquisition, disease suppression and productivity, but if and how host development impacts the assembly, functions and microbial interactions of crop microbiomes are poorly understood. Here we examined both bacterial and fungal communities across soils (rhizosphere and bulk soil), plant epiphytic and endophytic niches (phylloplane, rhizoplane, leaf and root endosphere), and pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
(185 reference statements)
1
4
0
Order By: Relevance
“…In the results, the pattern of niche driving to microbial was supported by some studies on crops (Xiong et al, 2021a, b) and wild plants (Cregger et al, 2018; Zheng and Gong, 2019; Wang et al, 2022) from local to regional areas. However, recent studies have shown that fungal compositional variance is better predicted by sampled sites than by microhabitats in regional areas (Bernard et al, 2021; Thiergart et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In the results, the pattern of niche driving to microbial was supported by some studies on crops (Xiong et al, 2021a, b) and wild plants (Cregger et al, 2018; Zheng and Gong, 2019; Wang et al, 2022) from local to regional areas. However, recent studies have shown that fungal compositional variance is better predicted by sampled sites than by microhabitats in regional areas (Bernard et al, 2021; Thiergart et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…S5), further indicating that the rhizosphere act as a hotspot of plant-microbe-soil interactions. However, another study found that plant bacterial communities are gradually filtered and enriched from bulk soils to plant niches (Xiong et al, 2021b). This could be primarily attributed to the harsher soil conditions (low nutrients and soil moisture) in the root zone and bulk soil than in the rhizosphere in the desert ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from 0.25 g of each soil sample by using the PowerSoil ® Kit(100) and the concentration of extracted DNA was then determined by a NanoDrop 1000 spectrophotometer. Soil fungi were amplified fungal ITS2region and selected primers pairs fITS7 (5’- GTGARTCATCGAATCTTTG-3’) and ITS4 (5’-AGCCTCCGCTTATTGATATGCTTAART-3’) ( Xiong et al., 2021 ). The 25 μL PCR reaction mixture contained 8.5 μL of sterile deionized water, 0.75 μL of each primer, 12.5 μL of KAPA Polymerase and 2.5 μL of diluted template DNA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 0.25 g of each soil sample by using the PowerSoil ® Kit(100) and the concentration of extracted DNA was then determined by a NanoDrop 1000 spectrophotometer. Soil fungi were amplified fungal ITS2region and selected primers pairs fITS7 (5'-GTGARTCATCGAATCTTTG-3') and ITS4 (5'-AGCCTCCGCTTATTGATATGCTTAART-3') (Xiong et al, 2021). The 25 mL PCR reaction mixture contained 8.5 mL of sterile deionized water, 0.75 mL of each primer, 12.5 mL of KAPA Polymerase and 2.5 mL of diluted template DNA.…”
Section: Molecular and Bioinformatics Analysismentioning
confidence: 99%